MODELLING MIGRATION ATTEMPTS AND THE ROLE OF GENDER IN ALBANIA - Litchfield, Julie; Reilly, Barry (Economic Annals, 2009)
This paper uses the 2002 Albanian Living Standards Measurement Survey to model whether an individual has attempted to migrate conditional on having previously considered migrating. The study addresses the methodological concerns that arise from potential selection bias and empirical issues associated with gender differences. We test for the presence of selection bias using a bivariate probit and apply an Oaxaca-style decomposition technique to analyse gender differentials in the conditional probability of attempted migration. We focus on the roles an individual’s living standard, geographic location and local labour market conditions exert on the attempt to migrate. Our empirical findings suggest that there are significant differences in both the conditional probability of attempting to migrate and the relative importance of determining factors across gender.